Improved fatigue strength of additively manufactured Ti6Al4V by surface post processing - Kahlin, M.; Ansell, H.; Basu, D.; Kerwin, A.; Newton, L.; Smith, B.; Moverare, J.J. (International journal of fatigue, 2020)
•Surface post processes are needed for PBF Ti6Al4V to achieve high fatigue strength.•Centrifugal finishing of L-PBF Ti6Al4V gave the highest fatigue strength.•Laser polished material had reduced fatigue strength although low surface roughness. A major challenge for additively manufactured structural parts is the low fatigue strength connected to rough as-built surfaces. In this study, Ti6Al4V manufactured with laser powder bed fusion (L-PBF) and electron beam powder bed fusion (E-PBF) have been subjected to five surface processing methods, shot peening, laser shock peening, centrifugal finishing, laser polishing and linishing, in order to increase the fatigue strength. Shot peened and centrifugal finished L-PBF material achieved comparable fatigue strength to machined material. Moreover, the surface roughness alone was found to be an insufficient indicator on the fatigue strength since subsurface defects were hidden below smooth surfaces.